EFEK BERKUMUR REBUSAN DAUN SIRIH HIJAU (Piper betle Linn.) 10% TERHADAP PERTUMBUHAN Streptococcus Î± haemolytic PADA PLAK GIGI - , SITI FATIMAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Green betel leaf (Piper betle Linn.) as traditional medicine contains flavonoid, eugenol, cavicol, tannin, catechin, flour which have bacteriostatic effect. Flavonoid, eugenol, cavicol and tannin inhibit bacteria by coagulating the bacterial protein and distrupt permeability of cell wall. Cathechin and fluor contained in piper betle leaf can distrupt hidrofobicity of bacteria and distrupt the adhesion. Dental plaque is main cause of dental caries with microorganism as the main component. One of microorganism is Streptococcus Î± haemolytic as early stage bacteria in the plaque formation. The aim of this study was to assess the effect of gargling with 10% green betel leaves decoction against the growth of Streptococcus Î± haemolytic in dental plaque. Twenty female subjects aged 19-23 years old and had a good OHI - S were divided into 2 groups. The treatment group was instructed to gargle with 10% green betel leaves decoction and control group was gargled with distilled water for 5 consecutive days. Subjectâs plaque was taken 2 times, first was before the treatment and second was on day 5 after treatment. Approximately 1mg plaque was collected and then cultured on blood agar media and incubated at 370C for 48 hours. Colony counter was used to count the bacterial colony and then converted into CFU/ml. The data was analyzed using independent T-test. The results of this study showed that there were significant different between treatment and control groups ( p < 0.05 ) . Based on this result, it can be concluded that gargled with 10% green betel leaves decoction could inhibit the growth of Streptococcus Î± haemolytic bacteria in dental plaque.